Implementation of Minister of Home Regulation (Permendagri) Number 114 of 2014 in Village Development Planning Management - Fatria Khairo; Firman Freaddy Busroh (GoAcademica Research & Publishing, 2023)
This study is inspired by the fact that management in the planning stage, as the initial step in village development, plays an important role. This is in accordance with and is a form of implementation of Minister of Home Affairs Regulation Number 114 of 2014 concerning Village Development Guidelines. The function of management is to achieve planning goals, organizers who are ready to carry out planning steps so that everything runs smoothly and well. This will also have an impact on village development which will be successful, effective and of course efficient. This research aims to describe the implementation of village development planning management in accordance with Minister of Home Affairs Regulation No. 4 114 of 2014. This research is included in the library research category where the primary data source is books related to village development planning management. Meanwhile, supporting (secondary) data is literature that is still related to this research. In the data analysis technique, the author uses a descriptive method, namely research that seeks to describe and interpret what exists, opinions that are growing, ongoing processes, consequences or effects that occur or developing trends. In this research, the results showed that planning in village development is appropriate and a manifestation of the implementation of Minister of Home Affairs Regulation Number 114 of 2014. There is one thing in the village development planning process that must not be forgotten, namely management. Management functions in village development planning are planning, organizing, mobilizing or directing and controlling.